Is Disrupted Nucleotide-Substrate Cooperativity a Common Trait for Cushing's Syndrome Driving Mutations of Protein Kinase A?. Issue 18 (3rd September 2021) - Walker, Caitlin; Wang, Yingjie; Olivieri, Cristina; V.S, Manu; Gao, Jiali; Bernlohr, David A.; Calebiro, Davide; Taylor, Susan S.; Veglia, Gianluigi
Graphical abstract: Highlights: A Cushing's disease mutation of protein kinase A disrupts nucleotide-substrate binding cooperativity. The E31V mutation attenuates the intramolecular allosteric network mapped by NMR. The reduction of intramolecular allostery is log-linearly correlated with the loss of binding cooperativity. Abstract: Somatic mutations in the PRKACA gene encoding the catalytic α subunit of protein kinase A (PKA-C) are responsible for cortisol-producing adrenocortical adenomas. These benign neoplasms contribute to the development of Cushing's syndrome. The majority of these mutations occur at the interface between the two lobes of PKA-C and interfere with the enzyme's ability to recognize substrates and regulatory (R) subunits, leading to aberrant phosphorylation patterns and activation. Rarely, patients with similar phenotypes carry an allosteric mutation, E31V, located at the C-terminal end of the αA-helix and adjacent to the αC-helix, but structurally distinct from the PKA-C/R subunit interface mutations. Using a combination of solution NMR, thermodynamics, kinetic assays, and molecular dynamics simulations, we show that the E31V allosteric mutation disrupts central communication nodes between the N- and C- lobes of the enzyme as well as nucleotide-substrate binding cooperativity, a hallmark for kinases' substrate fidelity and regulation. For both orthosteric (L205R and W196R) and allosteric (E31V) Cushing's syndrome mutants, the loss of binding cooperativity is proportional to the density of the intramolecular allosteric network. This structure–activity relationship suggests a possible common mechanism for Cushing's syndrome driving mutations in which decreased nucleotide/substrate binding cooperativity is linked to loss in substrate fidelity and dysfunctional regulation.